2018
DOI: 10.3846/transport.2018.1574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Speed Reduction Markings in Highway Tunnels

Abstract: As typical weak visual reference systems, highway tunnels have low illumination, monotonous environment and few references, which may cause severe visual illusion and reduce drivers' speed perception ability. Thus, drivers tend to underestimate their driving speed, which may induce speeding behaviours that result in rear-end collisions. The cost-effective pavement markings installed on both sides of the lane or shoulder may make drivers overestimate their speed. This perception can help ensure safe driving and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…In the entrance zones, the driving speed had a noticeable difference in the situation of NSRMs and SRMs. Previous studies reported that speeds were significantly affected by SRMs [27][28][29]. In this study, a similar downward trend has performed in the situation of NSRMs and SRMs, but a lower speed occurred in case of SRMs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the entrance zones, the driving speed had a noticeable difference in the situation of NSRMs and SRMs. Previous studies reported that speeds were significantly affected by SRMs [27][28][29]. In this study, a similar downward trend has performed in the situation of NSRMs and SRMs, but a lower speed occurred in case of SRMs.…”
Section: Discussionsupporting
confidence: 86%
“…TRSMs, LSRMs, and CASMs can all produce the visual illusions that affect the drivers' speed perception [27][28][29], or warn the drivers to reduce speed, as well as raise the drivers' vigilance [20]. Figure 3) was used to collect the real-time data, including operation data of vehicles (speed, acceleration, etc.)…”
Section: L8 L7 L6 L5 L4 L3 L2 L1mentioning
confidence: 99%
“…This causes some difficulties during visualization where smooth movements are required for realistic representation. Similar issues are found when using such models in driving simulators, which often use 3D virtual reality interfacing in order to provide realistic visualization for evaluation of driver responses (Wan et al 2018). Real-time and faster computation is easily achieved using the traffic microsimulation models, where the road network is a single road tunnel with surrounding road sections.…”
Section: Road Traffic Microsimulationmentioning
confidence: 98%
“…In China, speed reduction markings are not enforceable because the markings are characterized as non-intrusive speed control devices. Although many Chinese researchers [17, 18, 19, 20, 21, 22, 23] assume that speed reduction marking would make drivers believe that the lane becomes narrower which would generate visual illusion on drivers. However, such assumptions need more theoretical or empirical studies conducted based on the characteristics road specific in China.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study was to analyze the effects of sidewall markings in highway tunnels by observing how their angles and lengths affect the driver’s speed perception. The results had the reflection of Zöllner illusion suggesting the perception of lane width shrinks may induce deceleration behavior [21]. Recently, Ding et al performed a naturalistic field driving to study the effects of reverse linear perspective of transverse markings on car-following headway in China.…”
Section: Introductionmentioning
confidence: 99%